Dementia‐friendly community initiatives: An integrative review. Issue 11 (29th January 2019) - Shannon, Kay; Bail, Kasia; Neville, Stephen
Abstract: Aim: To synthesise international research conducted on dementia‐friendly community initiatives. Background: The number of people living with dementia is increasing as a result of population ageing. Impairments related to neurological changes, together with environmental challenges, result in disability for people who have dementia. Led by the World Health Organization and Alzheimer's Disease International, initiatives have been undertaken internationally to promote social inclusion for people who have dementia. Communities where people with dementia are able to remain socially included are known as dementia‐friendly communities. Design: An integrative review of the literature. Methods: Scopus, MEDLINE, Web of Science and CINAHL Plus via Ebsco databases were searched for relevant articles. The PRISMA framework guided the article search and screening; reporting is in accordance with the PRISMA guideline. Eight eligible studies were identified. The methodological quality of the eligible studies was evaluated using the MMAT checklist. The matrix method was used to extract, abstract and analyse the data. Results: Of the eight studies reviewed, five were from the UK and one each from Australia, New Zealand and Canada. Four major concepts were identified in the literature, and these are characteristics of dementia‐friendly communities, facilitators and barriers to community engagement for people with dementia, strategies for developing dementia‐friendly communities and challenges encountered when developing dementia‐friendly communities. Conclusion: People with dementia are at the centre of dementia‐friendly initiatives, and these foster social inclusion. Collaborations and partnerships enhance development of dementia‐friendly communities; however, lack of resources and difficulty ensuring representation of marginalised groups provide challenges. Relevance to clinical practice: An understanding of the impact of marginalisation and inequality on community participation for people with dementia is important for practitioners, enabling them to support those people. Senior nurses with this understanding can ensure services are able to meet the needs of a growing population with dementia.